Dinamika Perubahan Perilaku Pembelian Impulsive Konsumen Dimasa Pandemik Covid-19 - Dewi Noor Susanti; Sulis Riptiono (Jurnal Bisnis dan Ekonomi, 2022)
This study aims to determine the dynamics of consumer behavior in relation to unplanned purchases during the Covid-19 pandemic. The study was conducted by testing the concept of impulse buying by using three variables as antecedents. Data were collected using a questionnaire with a sample of 100 respondents who visited and shopped at the Thrift Store in Jogjakarta and were taken using purposive sampling technique. Multiple regression analysis was used to test the results of the study. The results showed that the hedonic shopping motivation, Money availability, and Positive emotion variables were partially or simultaneously proven to be variables that could increase consumers' impulsive buying behavior. While Positive emotion is a variable that has the greatest influence in increasing impulse buying.